Awareness Regarding Preventive Measures of Avian Influenza Among the Adult People of Thimi Municipality, Nepal (Kathmandu University Medical Journal, 2014)
Background Avian influenza is considered as a threat to global public health. Prevention and control depends on the awareness of the general population as well as high risk-groups. The avian influenza should be viewed more seriously because it may lead to pandemic influenza when the virus mutates its strain with the common human influenza. Thus, this study aims to explore the awareness regarding preventive measures of avian influenza among the adult population of Thimi Municipality. Objective The objective of this study was to explore awareness regarding preventive measures of avian influenza among the adult population of Thimi Municipality. Methods It is a cross-sectional, population based study. It was carried out in Thimi Municipality from May 15 to June 15, 2012. Pre tested structured questionnaire was used for face to face interview with randomly selected 250 subjects. Results Out of 250 subjects, 123 (49.2 %) were males. The mean age of subjects was 36 ± 11.8 year. Among total subjects, 94.4 percent had heard about avian influenza. The main source of information was television (94.1%). Majority of subjects (84.9 %) thought that keeping infected birds and poultry as the mode of transmission followed by eating not well cooked poultry meat (82.8 %). Out of total study subjects, 165 (66.0 percent) mentioned fever and 138 (55.2 percent) thought fatigue as the signs and symptoms. As for knowledge about preventive measures, majority (85.6%) stated that cleaning the surfaces that had come in contact with the poultry could prevent the disease and 83.2 % had knowledge that the infection could be prevented by washing hands with soap and water after poultry handling. Awareness regarding preventive measures was found significantly low in females, middle adults, illiterates, and house wives. Conclusion The awareness regarding avian influenza was quite satisfactory among the adult people of Thimi Municipality. However level of awareness was seen lower in female, illiterate and middle adult. So that along with large scale mass education, there should be specific health education program for the specific group of population. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11026 Kathmandu University Medical Journal Vol.11(1) 2013: 45-49